THE EFFECT OF EM4 PROBIOTIC ADMINISTRATION FOR GROWTH AND SURVIVAL OF VANAME SHRIMP (Litopenaeus vannamei) - Lalu Wahyu Wilisetyadi; Dewi Nuraini Setyowati; Fariq Azhar (Aquaculture Department, University of Mataram, 2022)
Vannamei shrimp is a shrimp that has high economic value in Indonesia. The poor aquatic environment can reduce shrimp growth rates and stress and cause death, and efforts to improve water quality by giving Probiotics EM4. Probiotic EM4 contains beneficial bacteria that can improve shrimp's digestive system, decompose organic matter in the waters, control the growth of pathogenic bacteria, and improve water quality. The experimental parameters included total hemocyte count (THC), differential hemocyte count (DHC) consisting of hyaline cells, granule cells, and semi-granule cells, and phagocytic activity (AF). The study was carried out for 69 days using vanamei shrimp with PL 30. This study used four treatments and three replications, namely treatment P0 (without giving probiotic EM4), P1 (giving probiotic EM4 at a dose of 0.5 ml/L), P2 (giving probiotic EM4 at a dose of 1.5 ml/ L), P3 (giving probiotic EM4 dose of 2.5 ml/L). The study's results proved that the administration of probiotic EM4 on the maintenance medium had a significant effect (P<0.05) on THC, DHC, and AF. At THC, the highest value was at P3 with a value of 19.44 x 10 6 cells/ml, and the lowest was at P0 with a value of 11.01 x 10 6 cells/ml, then the DHC values such as hyaline cells ranged from 51.34 – 65.81%, granule cells ranged from 21.33 – 30.4%, semi-granular cells ranged from 12.84 – 18.24%. And then for the highest AF value at P3 with a value of 67.97% and the lowest P0 with a value of 49.34%